Socialization of the Use of Chat GPT in Increasing Village Community Resources - Ferine, Kiki Farida; Nadriati, Sri; Arif , Muhammad; Muharmi, Yulya; Kusuma, Chandra (Journal Of Human And Education (JAHE), 2024)
Recently, the topic of AI has been on the rise. The AI ​​hashtag was trending on Twitter. AI is an acronym for Artificial Intelligence or in Indonesian it is called artificial intelligence. AI is actually a field of computer science that focuses on solving cognitive problems or related to human intelligence, such as problem solving and pattern recognition. This ability, which seems like human intelligence, is controlled by a system controlled by a robot or computer. ChatGPT (Generative Pre-training Transformer) is an artificial intelligence system supported by AI that enables text-based conversational interactions. ChatGPT has various functions, including language translation, providing recommendations, increasing productivity, and assisting in improving village community resources. Therefore, the aim of this community service is to see the potential for using ChatGPT to help improve Village Community Resources in Aek Pancur Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra. In obtaining the data used were observation and literature review. This service activity is an educational effort to use ChatGPT to help increase community resources in Aek Pancur Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra. This effort was motivated by the lack of knowledge about the use of AI (Artificial Intelligence), especially ChatGPT in the community, which could increase the resources of the Aek Pancur village community itself. As a form of the author's thoughts, the efforts and breakthroughs made are offered, which can provide real benefits for the people of Aek Pancur Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra in obtaining the latest information and actively participating in village development.